EVALUATION OF FACTORS AFFECTING LEVELS OF SATISFACTION FROM MUNICIPAL SERVICES: THE CASE OF İZMİR MUNICIPALITY - İlker DAŞTAN (Fırat University, 2019)
In recent years, municipalities with significant changes in their structure and functioning have begun to give more importance to the quality of service provided to the community and to the satisfaction from these services. Municipalities are the leading units in the case of public service for local citizens as the most important institution of local governments. They are expected to thoroughly consider the expectations of their citizens and provide service in accordance with these expectations. There are significant differences in the expectations of citizens from municipal services and thus satisfaction of the citizens. The aim of the study is to measure satisfaction levels of citizens residing in town of Izmir from municipal services and to determine several personal, socio-economic and demographic factors affecting these levels of satisfaction by conducting a survey to 417 randomly selected citizens in 2014. The results demonstrate that there are statistically significant differences between levels of satisfaction and age, gender, marital status, and education levels of citizens. Men and married citizens are more satisfied from municipal services than their counterparts while the satisfaction levels decrease as citizens are younger or have higher education levels. Furthermore, the similarities and differences of this study from studies in literature are compared and several suggestions are made for improving local government policies.